Academic and Scientific Authorship Practices: A Survey Among South African Researchers. (October 2018) - Breet, Elsie; Botha, Jan; Horn, Lyn; Swartz, Leslie
Empirical studies of authorship practices in high-income countries have been conducted, while research on this issue is scarce in low- and middle-income countries. A survey was conducted among South African researchers who have published in peer-reviewed journals, to explore their understanding of and ability to apply academic authorship criteria. A total of 967 researchers participated in the survey; 88% of respondents had knowledge of academic authorship criteria, while only 52% found it easy to apply the criteria. More respondents experienced disagreement regarding who qualifies for coauthorship compared with authorship order (59% vs. 48%). Disagreement was mostly linked to different ways of valuing or measuring contributions. Level of agreement with academic authorship criteria was higher than the perceived ability to apply the criteria.